Multiplexed set of 10 microsatellite markers for identification of potato varieties - O. S. Kolobova; O. P. Maluchenko; T. V. Shalaeva; E. P. Shanina; I. A. Shilov; Ya. I. Alekseev; N. S. Velishaeva (Вавиловский журнал генетики и селекции)
Genetic identification of potato varieties is a demanded instrument for development of new cultivars registration system, protection of plant breeders’ rights, and variety homogeneity control. The most perspective approach for distinction and identification of varieties continues to remain the use of short tandem repeats. STR amplification with the subsequent high resolution electrophoresis allows such a unique characteristic of a variety to be obtained as the DNA profile. A large scale of samples requires the creation of a robust and time-saving technique based on fragment sizing. We selected 10 polymorphic STR loci of potato: STI0032, STG0016, STI0001, STI0004, STM1104, STM5127, STI0030, STI0033, STI0014, STM5114 and designed a multiplex panel for potato DNA profiling. Fluorescent labelling of primers and size distinction of amplicones allowed us to use one tube for PCR and capillary electrophoresis. We also modified the CTAB-protocol for DNA extraction from tubers and other parts of potato plants, the PCR mix recipe and the amplification protocol for good results. Using Genetic Analyzer allows the length of alleles to be defined with an accuracy of one nucleotide and digitized genetic profiles to be developed. We created a unique DNA profile for each of 40 varieties and 23 breeding lines from Russia and other countries and evaluated the homogeneity of 8 varieties. The proposed technique оf potato DNA profiling allows a large number of samples to be rapidly analyzed in the 96-well plate format.